Chromatic Numbers of Suborbital Graphs for the Modular Group and the Extended Modular Group - Wanchai Tapanyo; Pradthana Jaipong (Journal of Mathematics)
This research studies the chromatic numbers of the suborbital graphs for the modular group and the extended modular group. We verify that the chromatic numbers of the graphs are 2 or 3. The forest conditions of the graphs for the extended modular group are also described in this paper.